2013
DOI: 10.1007/s10461-013-0650-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Linkage to Care and Engagement in Care for Newly Diagnosed HIV-Positive Adolescents Within Fifteen Adolescent Medicine Clinics in the United States

Abstract: Early linkage to care and engagement in care are critical for initiation of medical interventions. However, over 50% of newly diagnosed persons do not receive HIV-related care within 6 months of diagnosis. We evaluated a linkage to care and engagement in care initiative for HIV-positive adolescents in 15 U.S.-based clinics. Structural and client-level factors (e.g. demographic and behavioral characteristics, clinic staff and location) were evaluated as predictors of successful linkage and engagement. Within 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 29 publications
2
74
0
Order By: Relevance
“…As a best practice for HIV care, linking PHAs to care resulted in an urgency to connect PHAs to care, which in turn minimized the loss to follow-up. Without transition support, retention in care may be suboptimal; studies have demonstrated that about 50% of newly diagnosed persons living with HIV are not linked to care within 6 months of their diagnosis (Philbin et al, 2013). By linking PHAs to care, both their immediate and long-term concerns were addressed.…”
Section: Discussionmentioning
confidence: 99%
“…As a best practice for HIV care, linking PHAs to care resulted in an urgency to connect PHAs to care, which in turn minimized the loss to follow-up. Without transition support, retention in care may be suboptimal; studies have demonstrated that about 50% of newly diagnosed persons living with HIV are not linked to care within 6 months of their diagnosis (Philbin et al, 2013). By linking PHAs to care, both their immediate and long-term concerns were addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, young sexual minority males are less likely than older MSM to have received an HIV test and the least likely out of any age group to be linked to HIV care 67891011121314 . Despite research indicating that nearly half of gay and bisexual male high school students have had sexual intercourse 1 little is known about attitudinal and experiential factors facilitating or impeding youth seeking and receiving health services for prevention, detection and treatment of HIV and STIs.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-level structural factors refer to the immediate demographic and social context within which individuals' interactions with others take place (e.g., insurance status and knowledge of health services). 29,30 …”
mentioning
confidence: 99%